Interleukin 3-dependent survival by the Akt protein kinase - Songyang, Zhou (The National Academy of Sciences of the USA, 1997)
Interleukin 3 (IL-3)-dependent survival of hematopoietic cells is known to rely on the activity of multiple signaling pathways, including a pathway leading to activation of phosphoinositide 3-kinase (PI 3-kinase), and protein kinase Akt is a direct target of PI 3-kinase. We find that Akt kinase activity is rapidly induced by the cytokine IL-3, suggesting a role for Akt in PI 3-kinase-dependent signaling in hematopoetic cells. Dominant-negative mutants of Akt specifically block Akt activation by IL-3 and interfere with IL-3-dependent proliferation. Overexpression of Akt or oncogenic v-akt protects 32D cells from apoptosis induced by IL-3 withdrawal. Apoptosis after IL-3 withdrawal is accelerated by expression of dominant-negative mutants of Akt, indicating that a functional Akt signaling pathway is necessary for cell survival mediated by the cytokine IL-3. Thus Akt appears to be an important mediator of anti-apoptotic signaling in this system.